Gender and identity in Franz Grillparzer's classical dramas figuring the female - Ellis, Alicia E. 1976- (Lexington Books, 2021)
"Gender and Identity in Franz Grillparzer's Classical Plays explores language as a cultural document for an intervention into the ways that female alterity is framed in the ancient world. Grillparzer creates a new way of being that is primarily discursive in which the once unintelligible female figure may be known and heard"--
Keywords: Grillparzer, Franz -- 1791-1872; Geschlechtsidentität -- Motiv; Frau -- Motiv; Feministische Literaturwissenschaft; Drama; Grillparzer, Franz / 1791-1872 / Criticism and interpretation; Grillparzer, Franz / 1791-1872 / Characters; Women in literature; Gender identity in literature; Feminist literary criticism; Grillparzer, Franz / 1791-1872; Criticism, interpretation, etc